The structural model of cyberchondria based on personality traits, health-related metacognition, cognitive bias, and emotion dysregulation - Nasiri, Mohammad; Mohammadkhani, Shahram; Akbari, Mehdi; Alilou, Majid Mahmoud (Frontiers in Psychiatry, 2023)
Cyberchondria is excessive seeking for online health-related information related to increasing health anxiety and distress levels. The current study aimed at investigating the mediating role of health-related metacognition, cognitive bias, and emotion dysregulation in the relationship between personality traits and cyberchondria. Participants were 750 adults of 18+ years old who had access to the Internet (males = 43.8%, mean age = 33.82 ± 10.09 years and females=56/2%, mean age =34.37 ± 11.16 years). They voluntarily completed a questionnaire package which included the Cyberchondria Severity Scale (CSS), The revised NEO Personality Inventory (NEO-PI-R), the Difficulties in emotion regulation scale (DERS), The Meta-Cognitions about Health Questionnaire (MCQ-HA), and The Health Cognitions Questionnaire (HCQ). Structural equation modeling analyses (LISREL 8.80 software) revealed a full mediation of health-related metacognition, cognitive bias, and emotion dysregulation in the relation between personality traits and cyberchondria. Fit indices demonstrated the desired fit of the model with the collected data (χ2 = 979.24, p <.001; NFI = 0.92, CFI = 0.93, GFI = 0.90, IFI = 0.93, RMSEA = 0.071, SRMR = 0.063). The results indicated that the present model could explain R2=54% of cyberchondria. These findings suggest that particularly health-related metacognition, cognitive bias, and emotion dysregulation could demonstrated a total mediating role in the correlation between personality traits and cyberchondria.